Shape and size of foveal avascular zone in normal subjects using optical coherence tomography angiography (OCTA): A retrospective analysis - Adeel Chaudhry; Muhammad Moin; Tayyaba Gul Malik; Mehreen Akram; Abdullah Irfan; Ahsan Mehmood (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the shape and size of foveal avascular zone in terms of perimeter, circularity, roundness and axial ratio using optical coherence tomography angiography. Method: The retrospective study was conducted at the Yaqeen Vison Clinic, Lahore, in August 2023, and comprised data from January 2020 to December 2022 of patients of either gender aged 17-84 years having best corrected visual acuity >6/6 and normal retina. Foveal avascular zone was measured using optical coherence tomography angiography. Perimeter, circularity, axial ratio and roundness were assessed. Only one eye of each subject was considered for analysis. Data was analysed using SPSS 25. Results: Of the 208 patients, 108(52%) were females and 100(48%) were males. The overall mean age was 56.55±16.6 years. There were 106(51%) right eyes and 102(49%) left eyes. Mean values for perimeter, circularity, axial ratio and roundness were 2.18±0.3mm, 0.93±0.12, 1.18±0.23and 8.09±1.41, respectively. There was a significant association of foveal avascular zone perimeter with age (p=0.001). Circularity, axial ratio and roundness did not have significant variations with age (p>0.05). Conclusion: Foveal avascular zone in Pakistani individuals was found to be larger, and there was more variation in foveal avascular zone size than shape, making shape a more reliable factor in retinal vascular diseases. Key Words: Fovea centralis, Retina, OCT, Fluorescein angiography.